TANGGUNG JAWAB NOTARIS DAN KEDUDUKAN PERJANJIAN NOMINEE DI INDONESIA - Ivana Ivana; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2022)
Agreement is a concrete event that can be seen from written or unwritten agreements, in Indonesia there are severaltypes of agreements, namely appointment agreements. The nomination agreement under Indonesian law can beclassified as an agreement that can lead to legal contraband. The appointment agreement has not been made in theCivil Code, but in fact the prospective agreement grows and develops in the community, the agreement is alsoincluded in the category of matchmaking or anonymous contracts. The appointment agreement can be interpreted asa statement of truth and a power of attorney, usually the agreement with the candidate is stated in the form of a deedof the parties, to strengthen the agreement, an authentic deed is made. This work uses a normative research methodwith a legislative approach, a case-by-case approach and a conceptual approach, for research purposes to analyzeand explain the notary's duties of wrongdoing committed by the parties in the agent's deed. responsible for theexistence of the nomination contract, only a notary who carries out according to his abilities and responsibilities inaccordance with the applicable rules, but if an unlawful act occurs, it will be returned to the maker of thenomination deed.